Incentive Structure of Financing a Project: An Islamic Finance Approach - Lone, Fayaz Ahmad; Quadir, Abdul (International Journal of Economics and Financial Issues, 2017)
Financing is an important component in any project. Without finance, it is impossible to run any project as it is considered the lifeblood of the business. But due to the presence of predetermined rate of interest, economists have provided alternative approach for financing the project. In this paper a model using Profit and Loss Sharing (PLS) system and comparison of it with the conventional financing model is developed. Thrust in this paper is towards establishing a new theoretical reasoning why PLS system is less frequently used in Islamic banking in terms of net worth of the borrower. It has been argued that agency problem like moral hazard is still acute in PLS system. An idea has been discuss to solve this problem using game theoretic tool. Keywords: Entrepreneur, Financing, Project, PLS, Model JEL Classifications: D92, L26